Google Trends and Disaster Risk Communications in The Seroja Tropical Cyclone Disaster Series in Indonesia - Budi Purwanto; Mario Beko Sihombing (International Journal of Seocology, 2023)
Internet users in Indonesia in early 2021 reached 202.6 million people, which was ranked third in Asia Pacific and internet penetration in Indonesia in early 2021 reached 73.7 percent. As a country that has various disaster threats, the Indonesian people are required to have awareness of the existing disaster risks. The form of public awareness that they are in a disaster risk area can be seen, among others, in efforts to increase their knowledge of disaster, one of which can be done by searching for news online through the google search engine. Google search engine is used by 97.65% of internet users in Indonesia or as many as 197.83 million users. This study aims to find out the search trends of Indonesian people before, during, and after the occurrence of a series of tropical cyclones seroja using Google Trends Analysis on three keywords, namely "Cyclone", "Tropical Cyclone", and "Tropical Cyclone Seroja". Before the disaster, the average daily trend of google on the three search keywords was 33.61; 12.90 and 0. During the disaster it was 31.03; 16.55; and 2.42, and after the disaster was 37.67; 15.23 and 2.71. Google's trend of tropical cyclone disaster in Indonesia increased after the disaster occurred. In the pre-disaster phase, early warnings delivered to the public by the authorities (BMKG) have not made the Google trend increase due to lack of coverage by the media, both local and national. When a disaster occurs, there is a significant increase in the trend. After a series of disasters, google search trends tend to be high during the emergency response phase. Disaster risk communication becomes a very urgent matter to be carried out with the help of mass media that reaches the community so that the risk due to tropical cyclone disasters can be reduced in the future.